Validation of a density dependent groundwater transport model using mass recovery rate - Sbarbati, Chiara; Colombani, Nicolò; Mastrocicco, Micol; Petitta, Marco (Italian journal of engineering geology and environment, 2013)
In this short note is described the validation process of a density dependent groundwater transport model, previously implemented and published, using the mass recovery rate of dissolved Total Petroleum Hydrocarbons and Chloride from 67 pumping wells in a polluted site. A good fit between observed and calculated values was recorded, supporting the feasibility of flow and transport models validation in complex polluted sites where pump & treat remediation are applied and management strategies need to be rapid and robust.